QR Code based Multi factor Authentication Protocol for IoT Networks - B. Prema Sindhuri, M. Kameswara Rao (International Journal of Advanced Science and Technology, 2020)
In recent years, with rapid growth and development in Internet of Things(IoT) Technology using wireless communication networks. There are major applications like smart home, smart health care and smart transportation etc. Generally the IoT devices access the user private data, the security and privacy become a challenge. As we are having various authentication systems implemented for authorizing the user to get the access of device or to get the controls of device. Multi-factor authentication (MFA) provides great security to the device. QR code is a 2D matrix code provides high data store capacity than bar code. Now a days, QR code is applied in many applications like payment systems, security etc. The proposed architecture implements the security enabled IoT device, in order to get the access or controls it requires MFA which is encrypted QR code.